2002
DOI: 10.1149/1.1490359
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Aqueous Phenol Wastes Using Active and Nonactive Electrodes

Abstract: The electrochemical oxidation of acidic aqueous phenol wastes has been studied using boron-doped diamond thin-film ͑BDD͒ and AISI 304 stainless steel ͑SS͒ electrodes. A voltammetric study shows marked differences in the electrochemical behavior of these two electrodes. The surface of the SS electrodes undergoes significant changes when this material is used as the anode in the treatment of aqueous wastes, even in the potential region of electrolyte stability. These changes have important effects on the waste t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 26 publications
(25 reference statements)
3
45
0
1
Order By: Relevance
“…Tahar and Savall [44] mineralized phenol at Bi-doped PbO 2 on a Ti-metal oxide base; Borras et al [45] oxidized p-substituted phenols, also at Bi-doped PbO 2 , and found that although mineralization occurred, oxidation of the intermediate benzoquinone was the slow step of the overall process, a result comparable to the present findings. Of closest relevance to the present study, phenol was shown to be oxidizable at BDD [37]; in the potential region of water stability an electrode-fouling film was formed, but in the potential region of water decomposition oxidation of the substrate occurred by way of reactive intermediates (subsequently shown to be hydroxyl radicals formed at the surface of BDD [46]) and fouling did not occur [47].…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Tahar and Savall [44] mineralized phenol at Bi-doped PbO 2 on a Ti-metal oxide base; Borras et al [45] oxidized p-substituted phenols, also at Bi-doped PbO 2 , and found that although mineralization occurred, oxidation of the intermediate benzoquinone was the slow step of the overall process, a result comparable to the present findings. Of closest relevance to the present study, phenol was shown to be oxidizable at BDD [37]; in the potential region of water stability an electrode-fouling film was formed, but in the potential region of water decomposition oxidation of the substrate occurred by way of reactive intermediates (subsequently shown to be hydroxyl radicals formed at the surface of BDD [46]) and fouling did not occur [47].…”
Section: Resultssupporting
confidence: 50%
“…BDD and Ti/SnO 2 are characterized as anodes at which water hydrolysis affords initially adsorbed hydroxyl radicals [35][36][37]. Oxidation of the substrate therefore occurs by attack of hydroxyl radicals, any intermediate products formed are themselves susceptible to oxidative attack.…”
Section: Resultsmentioning
confidence: 99%
“…Cerium may play the role of electrocatalytic active centers, and strengthen electron transfer on the interface of the solution and the electrode, which is ascribed to its unique outer electronic structure (Liu et al, 2011). The electrons at the 4f orbital of Ce are not fully occupied, which could occupy the 5d orbital and become valence electrons (Can˜izares et al, 2002). CNT is a material with good electrical conductivity, high chemical stability, large specific surface area and extraordinary electrochemical properties.…”
Section: Electro-catalytic Degradation Of M-npmentioning
confidence: 99%
“…A general scheme for the electrochemical degradation of organic compounds on metal oxide electrodes (MO x ) has been proposed [15]. H 2 O is assumed to be discharged on the anode to form adsorbed hydroxyl radicals:…”
Section: Introductionmentioning
confidence: 99%